2008
DOI: 10.5194/angeo-26-619-2008
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and fields in the wake of Rhea: 3-D hybrid simulation and comparison with Cassini data

Abstract: Abstract. Rhea's magnetospheric interaction is simulated using a three-dimensional, hybrid plasma simulation code, where ions are treated as particles and electrons as a massless, charge-neutralizing fluid. In consistency with Cassini observations, Rhea is modeled as a plasma absorbing obstacle. This leads to the formation of a plasma wake (cavity) behind the moon. We find that this cavity expands with the ion sound speed along the magnetic field lines, resulting in an extended depletion region north and south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 43 publications
11
72
1
Order By: Relevance
“…The first is that the properties of the plasma deposited on a moon's trailing hemisphere are uniform everywhere across this hemisphere. Simulations have shown that this is generally valid at least for Rhea [Roussos et al, 2008]. Farrell et al [2007], however, used equations by Samir et al [1983] suggesting that a density perturbation from the wake should propagate also upstream with the sonic speed, leading to a density (temperature) dropout (enhancement) even before the wake boundary.…”
Section: Validity Of the Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first is that the properties of the plasma deposited on a moon's trailing hemisphere are uniform everywhere across this hemisphere. Simulations have shown that this is generally valid at least for Rhea [Roussos et al, 2008]. Farrell et al [2007], however, used equations by Samir et al [1983] suggesting that a density perturbation from the wake should propagate also upstream with the sonic speed, leading to a density (temperature) dropout (enhancement) even before the wake boundary.…”
Section: Validity Of the Assumptionsmentioning
confidence: 99%
“…It is also important that none of these models capture the electron dynamics in the wake, where some peculiar measurements are reported, such as extended depletions of very energetic electrons (>10 keV) or enhancements of 1-5 keV electrons in the wake center [Jones et al, 2008]. In addition, because of the low plasma speeds, the plasma distribution in the wake has a much different structure parallel to and perpendicular to the magnetic field [Roussos et al, 2008]. This requires that the wakeside hemisphere potentials be mapped in three dimensions.…”
Section: Application Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhea is an unmagnetised body and acts to absorb incident magnetodisk plasma [Khurana et al, 2008;Roussos et al, 2008]. Ionised material can be directly picked up by the motional electric field and form "pickup ion" current systems which, with the resulting j×B force and density gradients associated with the plasma wake [Simon et al, 2012;Khurana et al, 2017], slows down the incident magnetoplasma causing field-line draping and Alfvén wings.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the model has been successfully applied to the interaction between the Martian ionosphere and the solar wind (Simon et al, 2007a;Bößwetter et al, 2007), to cometary plasma interactions (Bagdonat and Motschmann, 2002;Motschmann and Kührt, 2006) and to the plasma environment of weakly magnetized asteroids (Simon et al, 2006a). Within the framework of the Cassini mission, the very weak magnetic field perturbations observed in the wakes of Saturn's icy satellites Tethys and Rhea have been successfully reproduced as well (Roussos et al, 2008;Simon et al, 2009b). Recently, a first application of our hybrid code to the plasma interaction of Enceladus has been presented at the AGU Fall Meeting (Kriegel et al, 2008;Kriegel, 2009).…”
Section: Model Description and Input Parametersmentioning
confidence: 90%